Role of Multidetector Computed Tomography in Clinically Suspected Cases of Small- and Large-bowel Obstruction - Iram Saifi; Shivali Kashikar; Pratapsingh H. Parihar; Gaurav Vedprakash Mishra; Mayur Wanjari (Journal of the Scientific Society)
This review was conducted to assess the function of multidetector computed tomography (MDCT) in cases of acute small intestinal obstruction with clinical suspicion. We looked through the electronic MEDLINE, EMBASE, Cochrane, and PubMed databases. The bibliographies of all pertinent articles and books were also meticulously searched. According to the inclusion and exclusion criteria, the appropriate articles were picked. To make the search procedure more sensitive while finding research, the Medical Subject Heading terms were developed. Some of these words included “MDCT,” “small-bowel obstruction,” “large-bowel obstruction,” and “intestinal obstruction.” When determining the obstruction’s source, MDCT is incredibly sensitive and precise. In addition, to identify intrinsic gastrointestinal pathology, MDCT can identify several related and incidental findings that are not clinically suspected.